Molecular Functionalization of Carbon Nanomaterials for Immuno-diagnosis of Cancer. (2016) - Singh, Anu; Choudhary, Meenakshi; Kaur, Satbir; Singh, Surinder P.; Arora, Kavita
Abstract: Carbon nanomaterials possess amazing physico-chemical properties with great potential for molecular functionalization to construct sensitive biosensors. We report a study of graphene oxide (GO) and carbon nanotubes (CNTs), to achieve, reusable, low cost and efficient immuno-sensing platform for lung cancer. Presence of biomarker (hTERT) was detected in concentration range of 10 ag mL -1 – 50 ng mL -1 and 5 fg mL -1 – 50 ng mL -1 using GO and CNT based nanocomposites, respectively. Subsequently, due to favourable attributes (peak current, stability, repeatability and reproducibility) achieved through CNT, simultaneous bianalyte detection of biomarkers (MAGE A2/A11)) expressed in serum, were demonstrated.